The Action is the Form Victor Hugo’s TED Talk* - Easterling, Keller (2018)
Space is a technology. Buildings and the cities they inhabit have become infrastructural— mobile, monetised networks. For the world’s power players, infrastructure space is a secret weapon. If Victor Hugo came back to give a TED talk, he might assert that architecture, once killed by the book, is reincarnate as something more powerful still— as information itself. If this space is a secret weapon, is it a secret best kept from those trained to make space?Keywords: achitecture; globalization; information; infrastructure; urban development.* Strelka Press, 2012